UKF Estimation Method of Centroid Slip Angle for Vehicle Stability Control - Wang, Pan; Fan, Xiaobin; Chen, Xinbo; Yi, Juean; He, Shuwen (International journal of control, automation, and systems, 2023)
Vehicle center of sideslip angle is an essential parameter in vehicle stability control system. In view of the current problems is taken as the research object including low estimation accuracy and poor real-time performance of the current centroid sideslip angle, the four-wheel motor driven electric vehicle. The estimation problem of the sideslip angle is studied in-depth when the vehicle is in a nonlinear state. In addition, an Unscented Kalman Filter (UKF) estimation method is proposed to reduce observation error and improve the practicability of the estimation system. First of all, the research starts with building a 7-degree-of-freedom vehicle model which is based on the Dugoff tire model. Then, after measuring the state parameters, the UKF algorithm is used to estimate the sideslip angle. By comparing with the Extended Kalman Filter (EKF) algorithm, it is confirmed that the estimation method can not only better estimate the center of sideslip angle in real time, but also greater improve the handling stability of the vehicle in the driving state. Besides, the effectiveness of the algorithm is further verified by the real vehicle road test.